2009
DOI: 10.1007/s10533-009-9313-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbon storage in post-mining forest soil, the role of tree biomass and soil bioturbation

Abstract: Carbon storage in aboveground tree biomass and soil organic matter (in depth of A layer development i.e., up to 20 cm) was studied in 22-32 year-old post-mining sites in the northwest of the Czech Republic. Four replicated sites afforested with different tree species (spruce, pine, larch, oak, lime or alder) were compared with sites left to natural regeneration which were dominated by aspen, birch and willow. No topsoil was applied at the sites; hence carbon accumulation resulted from in situ soil development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(88 citation statements)
references
References 42 publications
11
73
2
2
Order By: Relevance
“…These clear differences among ecosystems should be carefully considered when reconstructing forest soils and re-establishing nutrient stocks so as to ensure that restoration practices are tailor-made for each ecosystem type and its associated climatic conditions. Soil carbon is often used as a proxy for soil quality and is a good indicator of ecosystem recovery in post-mining soils (Frouz et al 2009;Turcotte et al 2009). Results from studies using chronosequences post-fire and post-harvesting indicate that soil carbon may return to pre-disturbance levels after about three decades in boreal forests (Norris et al 2009), while recovery of soil carbon in secondary tropical forests takes between 20 and 100 years (Martin et al 2013).…”
Section: Importance Of the Soil Organic Componentmentioning
confidence: 99%
See 1 more Smart Citation
“…These clear differences among ecosystems should be carefully considered when reconstructing forest soils and re-establishing nutrient stocks so as to ensure that restoration practices are tailor-made for each ecosystem type and its associated climatic conditions. Soil carbon is often used as a proxy for soil quality and is a good indicator of ecosystem recovery in post-mining soils (Frouz et al 2009;Turcotte et al 2009). Results from studies using chronosequences post-fire and post-harvesting indicate that soil carbon may return to pre-disturbance levels after about three decades in boreal forests (Norris et al 2009), while recovery of soil carbon in secondary tropical forests takes between 20 and 100 years (Martin et al 2013).…”
Section: Importance Of the Soil Organic Componentmentioning
confidence: 99%
“…Vegetation composition affects organic matter content and quality on reclaimed mine sites, in turn affecting the composition of microbial communities (Mummey et al 2002;Frouz et al 2009;Sorenson et al 2011;Macdonald et al 2012). Sorenson et al (2011) found that coniferous stands were linked with fungal presence, whereas aspen stands had a stronger bacterial component.…”
Section: Soil Microbial Processesmentioning
confidence: 99%
“…Organic matter plays a central role in the functioning of the overall soil ecosystem; as such, it is often used as a proxy for soil quality in soils undergoing reclamation (Frouz et al 2009;Turcotte et al 2009). Sandy soils, more so than their finer-textured counterparts, depend on organic matter to store nutrients and retain water, sustain a healthy biota and support plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Trees and shrubs usually provide a permanent vegetation cover on mined sites with little or no aftercare. Trees can help maintain or increase the soil organic matter, nitrogen fixation, or decrease the erosion rate, and improve soil physico-chemical and biological properties (Jha and Singh, 1991;Frouz et al, 2009). However, impact of trees on soil fertility will depend on their nutrient cycling characteristics, for example litter chemistry and decomposition (Byard et al, 1996).…”
mentioning
confidence: 99%